Development of Physics Edutainment Website to Improve Students’ Critical Thinking Skills During the Covid-19 Pandemic - Sania Salsabila; Abd. Kholiq (Universitas Muhammadiyah Purworejo, 2021)
During the Covid-19 pandemic that swept the world including Indonesia, and to improve students' critical thinking skills, it is necessary to have supporting media in the learning process as an edutainment website. This study intends to determine the validity of the edutainment website developed in physics lessons to improve student's critical thinking skills. The research method used is development research with the DDD-E model. This research was only limited to media development, and no practicality and effectiveness tests were carried out. In this study, the validity data were obtained from the results of validation by expert and were analyzed by descriptive quantitative using the category of Likert scale percentage. If the percentage of each aspect is ≥ 61%, then the edutainment website developed can be declared valid. The results of this study are the percentage of validity in the learning aspect of 90.30%, the material aspect of 90.56%, the media aspect of 88.65%, and the critical thinking aspect of 84.70%. Based on this, it can be concluded that the edutainment website is very valid so that it can be used as a physics learning media to improve students' critical thinking skills. The edutainment website can be an alternative learning media by utilizing information technology and hopefully in further research, it can apply edutainment website and perform practicality and effectiveness tests for learning both in class and distance learning